Listening to the beliefs of emerging churches five perspectives - Webber, Robert E.; Driscoll, Mark, 1970- (Grand Rapids, MI Zondervan, 2007)
Includes bibliographical references and index.
Keywords: Postmodernism -- religious aspects -- Christianity; Church renewal; Emergent church, the